2014
DOI: 10.1002/meet.2014.14505101052
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value of information sharing in online environments: User engagement and social reputation

Abstract: Consumer reviews have received much attention both in academia and industry, since it has been found that they have significant effects on people's decision‐making behaviors relating to online shopping or choosing services. The readers/visitors on various online communities where such reviews are posted evaluate the helpfulness of a review based on the extent to which the review is helpful in their information seeking and decision‐making tasks. However, it is often not clear what makes a review useful to a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…None of the previous studies fully reported ways in which prosumers can share knowledge with enterprises and public organizations (e.g., Aghamirian et al, 2013Aghamirian et al, , 2015Choi & Shah, 2014;Cui & Wu, 2015;Prahalad & Ramaswamy, 2004;Trejo et al, 2016). This study is complementary with findings related to paramount issues for prosumers' knowledge utilization in organizations presented in Figure 1, i.e.…”
Section: Not Supportedcontrasting
confidence: 43%
See 2 more Smart Citations
“…None of the previous studies fully reported ways in which prosumers can share knowledge with enterprises and public organizations (e.g., Aghamirian et al, 2013Aghamirian et al, , 2015Choi & Shah, 2014;Cui & Wu, 2015;Prahalad & Ramaswamy, 2004;Trejo et al, 2016). This study is complementary with findings related to paramount issues for prosumers' knowledge utilization in organizations presented in Figure 1, i.e.…”
Section: Not Supportedcontrasting
confidence: 43%
“…Four of them are paramount and are presented in Figure 1. Figure 1 presents that for the utilization of prosumers' knowledge in enterprises and public organizations it is important to know the ways of prosumers' knowledge sharing (Bryant, 2011;Choi & Shah, 2014). It is also crucial to know which incentives could encourage prosumers to engage in knowledge sharing (Ho & Kuo, 2013;Löcker et al, 2014), which ICT prosumers prefer for knowledge sharing (Bayram & Demirtel, 2014;Jiebing et al, 2013;Ritzer & Jurgenson, 2010), as well as in which business processes prosumers' knowledge can be used for their improvement (Gibbert, Leibold, & Probst, 2002;Prahalad & Ramaswamy, 2004).…”
Section: The Value Of Prosumers' Knowledge For Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Great opportunities for prosumers in the field of knowledge sharing create an online environment. Particularly, a social media development and their omnipresence caused that more and more enterprises and public organizations are trying to engage prosumers in prosumer-oriented projects and as a result -to obtain proper knowledge from prosumers (Choi & Shah, 2014;Jiebing, Bin, & Yongjiang, 2013). On one hand, this knowledge should be connected with organizations' expectations and enable them to develop and upgrade products, and may contribute to business process improvement (Aghamirian, Dorri, & Aghamirian, 2015;Trejo, Gutiérrez, & Guzman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The exchanging of knowledge is an important aspect of being a member of a community and customers voluntarily contribute knowledge increasing the prospective customer's awareness of the products and services offered by the business (Kumar, Aksoy, Donkers, Venkatesan, Wiesel, & Tillmanns, 2010). Further, businesses hold the desire to acquire information and customers have accelerated this rise in information sharing by posting reviews onto social media business web sites (Choi & Shah 2014). Customers appraise other customer's reviews, and customers appraise the business response.…”
Section: Introductionmentioning
confidence: 99%